Dampak Korean Wave (Hallyu) Bagi Budaya Indonesia Sebagai Dampak Dari Globalisasi Media - Winda Kustiawan; Erwan Efendi; Wahyu Candra; Putri Rahmadhani Zein (Peneliti.net, 2023)
Hallyu is a word that refers to the spread of popular culture in Korea internationally in various regions of the world. Usually, the presence of halyu encourages many people to learn Korean culture and language. With the globalization of media, this has caused the Korean wave and Hallyu to have a lot of influence on people's lives, especially among students and students. This paper is a paper that uses the literature study method. The source of information used in this paper is secondary information. The diffusion and acculturation of the Korean Wave in Indonesian culture has had two sides, both positive and negative. To overcome the problem of this cultural shift, the way that can be done is to provide guidance both from a psychological and religious perspective and to introduce Indonesian culture.